2017
DOI: 10.3389/fmars.2017.00209
|View full text |Cite
|
Sign up to set email alerts
|

Ecological-Economic Fisheries Management Advice—Quantification of Potential Benefits for the Case of the Eastern Baltic COD Fishery

Abstract: Fishing is a social and economic activity, and consequently socio-economic considerations are important for resource management. While this is acknowledged in the theory of Ecosystem-Based Management (EBM) and its sector-specific development Ecosystem-Based Fisheries Management (EBFM), currently applied fishery management objectives often ignore economic considerations. Year-to-year management, however, implicitly responds to short-term economic interests, and consequently, regularly resorts to tactical short-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…It is worth noting that maximising the fishery's net profits after 10 years requires to harvest hake below and sole above their respective F MSY reference points. The fact that fisherywide reference points (multispecies MSY or MEY) can lead to the under-or over-exploitation of individual stocks has already been highlighted by many authors [16,23,43,71,72]. Finally, we observed that the dynamic MEY is sensitive to the value of the discount rate, and, as expected, the higher the discount rate, the higher the associated harvest rates.…”
Section: Its Application To the Bay Of Biscay Demersal Mixed Fisherysupporting
confidence: 77%
See 1 more Smart Citation
“…It is worth noting that maximising the fishery's net profits after 10 years requires to harvest hake below and sole above their respective F MSY reference points. The fact that fisherywide reference points (multispecies MSY or MEY) can lead to the under-or over-exploitation of individual stocks has already been highlighted by many authors [16,23,43,71,72]. Finally, we observed that the dynamic MEY is sensitive to the value of the discount rate, and, as expected, the higher the discount rate, the higher the associated harvest rates.…”
Section: Its Application To the Bay Of Biscay Demersal Mixed Fisherysupporting
confidence: 77%
“…Based on the observation that ICES catch advice is often disregarded by EU member states' fisheries ministers [19,20], who are ultimately constrained by the social acceptability of their decisions, ICES has recognised the need to provide more integrated management advice [21] in order to increase the transparency of the decision-making process. The work presented in this paper contributes to the ongoing debate among the scientific community on how to incorporate social and economic considerations in their recommendations to decision-makers, with particular emphasis on mixed fisheries total allowable catch (TAC) advice [22,23].…”
mentioning
confidence: 99%
“…As discussed during relevant ICES workshops (e.g. WKDEICE) [ 48 ] such information might be used in different ways to inform stock assessment and advice [ 49 ]:…”
Section: Discussionmentioning
confidence: 99%
“…Larger scale international factors, which influence the Baltic fisheries, such as changes in prices at the world market, are manifold (Voss et al, 2017(Voss et al, , 2019. They can be summarized in the effect of trade, as fish has become a more and more globally traded commodity.…”
Section: Baltic Sea Fisheries Socio-economic System Indicatorsmentioning
confidence: 99%